2017
DOI: 10.1016/j.gpb.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Post-Transcriptional Gene Regulation by Long Non-Coding RNA

Abstract: Advances in genomics technology over recent years have led to the surprising discovery that the genome is far more pervasively transcribed than was previously appreciated. Much of the newly-discovered transcriptome appears to represent long non-coding RNA (lncRNA), a heterogeneous group of largely uncharacterised transcripts. Understanding the biological function of these molecules represents a major challenge and in this review we discuss some of the progress made to date. One major theme of lncRNA biology se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
537
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(543 citation statements)
references
References 111 publications
(160 reference statements)
4
537
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first study to show the role of lncMIF‐AS1 in cancer progression. LncRNAs are an extensive class of evolutionarily conserved non‐coding RNAs that are not translated into proteins; this “junk RNA” accounts for the major component of human transcripts . In the past few years, growing evidence suggests that lncRNAs play an important role in regulating many cell processes including proliferation, differentiation and apoptosis through regulation of the target gene at transcriptional, post‐transcriptional and epigenetic levels …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to show the role of lncMIF‐AS1 in cancer progression. LncRNAs are an extensive class of evolutionarily conserved non‐coding RNAs that are not translated into proteins; this “junk RNA” accounts for the major component of human transcripts . In the past few years, growing evidence suggests that lncRNAs play an important role in regulating many cell processes including proliferation, differentiation and apoptosis through regulation of the target gene at transcriptional, post‐transcriptional and epigenetic levels …”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of reports have shown that dysregulation of lncRNAs significantly contributes to the initiation and progression of gastric cancer through different molecular mechanisms . For example, lncRNA OR3A4 has been found to promote tumorigenicity and metastasis of gastric cancer through regulating the activation of PDLIM2, MACC1, NTN4 and GNB2L1 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Growing evidence indicates that lncRNAs exert pivotal functions in the development of various tumors, including HCC. 4,5 Growing evidence indicates that lncRNAs exert pivotal functions in the development of various tumors, including HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lncRNAs are also involved in the regulation of transcriptional processes whereby lncRNAs can aid in the recruitment of chromatin modifiers and aid in the formation of enhancer-like complex. Moreover, lncRNAs can also affect post-transcriptional processes via its interference with mRNA splicing processes and as a negative regulator in the inhibition of miRNA activity [6,7,9] .…”
Section: Long Non-coding Rna (Lncrna)mentioning
confidence: 99%